PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH BISNIS PERBANKAN (STUDI KASUS BANK BRI SYARIAH CABANG PEKANBARU) - ", Ismerelda; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Service Quality is how far the difference between reality and expectations of consumers with the services they received or acquired. loyalty is described as the desire of consumers to subscribe to the company continuously, buying and using products and services repeatedly, and recommend the company's products to others. Under these conditions, then a corporate banking services should be able to provide a quality service to its customers, in order to create customer satisfaction yhat will lead to these customers would be loyal to the product or services that exist in the bank. This research was conducted at Bank BRI Syariah branch Pekanbaru is located on the road Arifin Achmad, Pekanbaru. The purpose of this research was conducted to determine the effect of service quality on customer loyality on Bank BRI Syariah Branch Pekanbaru. In this research methodology is descriptive and quantitative with SPSS, where samples were used that customer bank BRI Syariah Pekanbaru is a minimum use of the bank services bank BRI Syariah products at least 1 year and as a source of information is the General Manager, Manager Operational. To determine the sample using the formula Slovin, sampling. Data collection through questionnaires and interviews. From the results of data analysis includes test validity, reliability, and simple linear regression, the quality of service in this study included five components of both the physical evidence, reliability, responsiveness, assurance, and caring. Each one has an indicator interrelated and positive effect on customer loyalty Bank BRI Syariah Branch Pekanbaru. Keywords: Service Quality, Customer Loyalty